Breaking the cycle of teacher shortages: What kind of policies can make a difference? - Darling-Hammond, Linda; Podolsky, Anne (Education Policy Analysis Archives, 2019)
Teacher shortages have recurred in the United States over many decades. This article introduces a special issue of EPAA that seeks to better understand the factors that contribute to the insufficient supply and inequitable distribution of qualified teachers, as well as the recurrences of teacher shortages. Together, the six articles in this issue help provide an empirical understanding of the current state of the supply, demand, and distribution of America’s public school teachers. This lead article provides an overview of the current status of teaching in the U.S. and outlines the volume’s findings about the key contributors to teacher supply, demand, and shortages of qualified teachers; the subject areas and locations in need of teachers; the determinants of high turnover for particular types of teachers; promising policies to recruit and keep teachers; and states’ attention to these policies. We hope the findings from this volume enable a better understanding of the obstacles and solutions to providing all students with high-quality teachers.